1987
DOI: 10.1016/0043-1354(87)90058-3
|View full text |Cite
|
Sign up to set email alerts
|

A general model for single-sludge wastewater treatment systems

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
517
1
33

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 637 publications
(561 citation statements)
references
References 9 publications
10
517
1
33
Order By: Relevance
“…Thus the step-feed reactor cascade does not improve the performance over that of a single reactor. This is surprising as the step-feed reactor cascade is common in the implementation of the activated sludge process [1,2]. We conclude that the step-feed reactor cascade is not appealing as a viable alternative to a conventional reactor design.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Thus the step-feed reactor cascade does not improve the performance over that of a single reactor. This is surprising as the step-feed reactor cascade is common in the implementation of the activated sludge process [1,2]. We conclude that the step-feed reactor cascade is not appealing as a viable alternative to a conventional reactor design.…”
Section: Resultsmentioning
confidence: 61%
“…An alternative reactor configuration is to use a stepfeed design [1,2]. This is similar to the standard configuration in that the product stream from the ith reactor flows into the i þ 1 ð Þth reactor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O modelo empregado reproduz as equações originalmente propostas por Henze et al (1987) mas não considera, no entanto, fenômenos de crescimento aeróbio de microrganismos autotróficos e de decaimento de microrganismos autotróficos nem outras parcelas de sólidos presentes no processo de lodos ativados.…”
Section: Modelo Dinâmicounclassified
“…The treatment of domestic wastewater during the treatment produced the water of good quality and there is an interest in its potential for drinking water supply (McCartey et al, 1984). The domestic wastewater contains readily biodegradable organic matter which is mainly composed of volatile fatty acids and low molecular weight carbohydrates that can pass through the cell membrane and be metabolized within minutes by the bacteria (Henze et al, 1987). It has been reported that microorganisms that bring about the decomposition of organic matter in wastewater can perform their activity efficiently in the activated sludge system (Barker and Dold, 1995).…”
mentioning
confidence: 99%